Effect of temperature and hydrogen on palm oil cracking over MCM-41/ZSM-5 composite catalysts - Abdul Karim, Siti Kartina (2006)
The diminishing source of non-renewable energy has spurred the interests of researchers to explore the possibility to use alternative sources. Catalytic cracking of vegetable oil to liquid fuels was studied by a number of individuals and the results were encouraging to continue with this study. Composite catalyst, MCM-41/ZSM-5 was used to catalytically convert palm oil to gasoline. The effects of temperature and hydrogen on palm oil cracking were investigated. Experiments were conducted in a fixed bed reactor at atmospheric pressure. Comparative performance of MCM- 41/ZSM-5 catalysts synthesized using different methods was evaluated before further testing. The variables tested were temperature (525 to 575Â°C) for cracking and hydrocracking reaction, palm oil to hydrogen ratio of 1:2 to 1:3.5, hydrotreatment flow rate (0.5 to 1.5 L/h) and hydrotreatment duration (1 to 3h). Catalysts used were characterized using X-ray Diffraction, Nitrogen Adsorption and Pyridine Infrared Spectrophotometry methods. The liquid and gaseous products were analyzed using Gas Chromatography. Conversion increased with temperature, whether in cracking or hydrocracking. Increase in hydrogen to palm oil molar ratio and longer catalyst hydrotreatment duration decreased palm oil conversion and gasoline selectivity. On the other hand, increasing the flow rate of catalyst hydrotreatment increased conversion, organic liquid productsâ€™ yield and gasoline selectivity. Aromatics were absent or nearly absent with hydrocracking and longer hydrotreatment duration. Gaseous products consisted of mainly C3 and C4 compounds